Kondisi Pencemaran Lingkungan Berdasarkan Parameter Mikrobiologis di Sekitar Muara Sungai Cimandiri, Teluk Pelabuhan Ratu, Jawa Barat - Nur Fitriah Afianti; Lies Indah Sutiknowati (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2020)
The Gulf waters of Pelabuhan Ratu are important waters for fisheries and tourism. However, currently  anthropogenic pollution carried by river flows threatens water quality, especially around the Cimandiri estuary. This study aims to analyze a water quality around Cimandiri estuary based on the abundance of fecal pollution indicator bacteria and patogenic bacteria on water samples taken from 15 stations. Fecal pollution indicator bacteria were enumerated using filtration method and plate count agar, while patogenic bacteria was detected using selective media and biochemical tests. The results of the study in March 2017 showed that domestic waste pollution occurred in Cimandiri estuary. The presence of pollution indicator bacteria colliform, E. coli and patogenic bacteria were found in the water column with varying density levels. The highest density of coliform bacteria was found in the mouth of Cimandiri estuary as much as 4.56x105 CFU / 100 ml and E. coli as much as  2.59x104 CFU/100 ml. Geomean of the total coliform bacteria and E. coli respectively 4.61x103 CFU/100 ml and 7.61x102 CFU/100 ml. The abundance of bacterial pollution indicators in Cimandiri Estuary has been already exceeded Indonesian water quality standard determined by the Ministry of Environment Decree. Patogenic bacteria i.e Vibrio sp. and Aeromonas sp. most found at Cimandiri Estuary.